Prevalence of and Risk Factors for Asthma in Off-Reserve Aboriginal Children and Adults in Canada - Hsiu-Ju Chang; Jeremy Beach; Ambikaipakan Senthilselvan (Canadian Respiratory Journal)
Only a few studies have investigated asthma morbidity in Canadian Aboriginal children. In the present study, data from the 2006 Aboriginal Peoples Survey were used to determine the prevalence and risk factors for asthma in Canadian Aboriginal children six to 14 years of age and adults 15 to 64 years of age living off reserve. The prevalence of asthma was 14.3% in children and 14.0% in adults. Children and adults with Inuit ancestry had a significantly lower prevalence of asthma than those with North American Indian and Métis ancestries. Factors significantly associated with ever asthma in children included male sex, allergy, low birth weight, obesity, poor dwelling conditions and urban residence. In adults, factors associated with ever asthma varied among Aboriginal groups; however, age group, sex and urban residence were associated with ever asthma in all four Aboriginal groups. The prevalence of asthma was lower in Aboriginal children and higher in Aboriginal adults compared with that reported for the Canadian population. Variation in the prevalence of and risk factors for asthma among Aboriginal ancestry groups may be related to genetic and environmental factors that require further investigation.